2011
DOI: 10.2308/accr.00000010
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organizational Absorptive Capacity in Strategic Use of Business Intelligence to Support Integrated Management Control Systems

Abstract: This study examines the influence of organizational controls related to knowledge management and resource development on assimilation (i.e., strategic integration and use) of business intelligence (BI) systems. BI systems use analytics and performance management concepts to leverage enterprise system databases and provide core management control system (MCS) capability. Our results indicate that organizational absorptive capacity (i.e., the ability to gather, absorb, and strategically leverage new external inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
175
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(181 citation statements)
references
References 87 publications
2
175
0
4
Order By: Relevance
“…BI systems use analytics and enterprise system databases. As a result, BI systems failed to support managerial decision making at both the strategic and operational levels, and hence failing to create business value through BI investments [17,18]. This empirical study found evidence for the importance of BI systems assimilation and the need for shared domain knowledge at the strategic and operational levels as the drivers of BI business value.…”
Section: Predictive Analytics and Decision-making Effectivenessmentioning
confidence: 85%
See 1 more Smart Citation
“…BI systems use analytics and enterprise system databases. As a result, BI systems failed to support managerial decision making at both the strategic and operational levels, and hence failing to create business value through BI investments [17,18]. This empirical study found evidence for the importance of BI systems assimilation and the need for shared domain knowledge at the strategic and operational levels as the drivers of BI business value.…”
Section: Predictive Analytics and Decision-making Effectivenessmentioning
confidence: 85%
“…Finally, the study found that operational managers' absorptive capacity matters to leveraging BI systems, although top management plays a significant role in effective deployment of BI systems but their influence is indirect. This suggests the key to leveraging BI systems is BI systems assimilation and use from the bottom up as opposed to the top down [17].…”
Section: Predictive Analytics and Decision-making Effectivenessmentioning
confidence: 99%
“…This issue was studied in the context of introducing PA -a BI-enabled forecasting process -since recently more and more companies have adopted PA tools on top of their ERP systems to support their sales forecasting. By addressing this topic, we responded to calls by Elbashir et al (2011) andGranlund (2011) to study the introduction of BI for management accounting purposes. Simultaneously, we also responded to Taipaleenmäki and Ikäheimo's (2013) call to address technology-driven changes in accounting, and investigate the crossroads and interfaces between the various functions, such as accounting and operations.…”
Section: Discussionmentioning
confidence: 99%
“…This current study is also motivated by the calls of Granlund (2011) and Elbashir et al (2011) which urge more research on BI-related aspects. Granlund (2011, 14-15) identified in his literature review a clear gap in the BI research.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, top management plays an important link in effective deployment of new technological know-how, but their impact is usually indirect and a function of the technology management (TM) absorptive capacity (Elbashir et al, 2011). Therefore, strategic and technology management should share their objectives, e.g., to help transforming the organization into a more effective, innovative and responsive form through the technology (Kamal, 2011).…”
Section: Introductionmentioning
confidence: 99%